Strategi pengembangan pelancongan Islamik di nusantara melalui model homestay patuh Syariah (MHPS) di Sabah - Suhailah Abdul Muina (UTM, 2024)
The strategy of developing Islamic tourism in the archipelago through the Shariah-Compliant Homestay Model in Sabah (MHPS) requires a holistic and planned approach. Key strategies include improving homestay infrastructure, providing courses for homestay owners in aspects of sharia compliance, effective digital marketing, collaboration with local communities, developing religiously oriented tourism packages, and the active involvement of religious institutions. The use of technology, an efficient management system, periodic evaluation, and an emphasis on the development of local skills are important aspects of developing a Syariah-compliant homestay model tourism strategy. This approach aims to create a tourism experience that meets Sharia principles by making MHPS in Sabah an attractive destination for Islamic tourists in the archipelago in particular and the world in general. Ensuring the success of this model depends on close cooperation between stakeholders and commitment to the improvement and continuity of the Islamic tourism industry. The research method used in this study is through in-depth interview techniques with 30 homestay operators in Sabah, literature highlights, and observation of facilities in the field. The results of the study show that the potential of Islamic tourism in Sabah and the archipelago is very large, but the accommodation infrastructure that complies with Sharia principles is still limited. Therefore, a comprehensive development strategy is needed to encourage the use of Shariah-compliant homestays (MHPS) as a suitable accommodation option for Muslim tourists. This development strategy needs to involve collaboration between the government, entrepreneurs, and the local community in developing MHPS by ensuring that aspects such as cleanliness, gender separation, and food preparation comply with halal standards. In addition, a strong marketing strategy emphasizing Islamic values for preserving the natural beauty of the archipelago needs to be implemented. The results of this study are expected to guide relevant parties in developing the potential of Islamic tourism in Sabah and the archipelago through MHPS widely, especially in Malaysia, Indonesia, Brunei Darussalam, and other Asian countries. The impact of the development of MHPS is seen to be able to increase the number of Muslim tourists from Asia and other parts of the world and provide economic benefits to the local community.